Multilingualism understanding linguistic diversity - Edwards, John 1947 December 3-
"Multilingualism is everywhere in our globalised society. Delving into the 'social life' of languages, John Edwards provides a brief yet compelling overview of multilingualism and its socio-cultural implications and consequences. Covering major topics including language origins, language death, lingua francas, pidgins, creoles and artificial languages, this book provides a complete introduction to what happens when languages meet. A vital primer for anybody interested in multilingualism, this new edition has been refreshed and updated, expanding its coverage and adding new topics such as linguistic imperialism, minority languages, and folk linguistics. A new chapter on recent developments covers the linguistic landscape, language planning, the 'new speaker' phenomenon and digital multilingualisms, and the addition of reflection questions at the end of each chapter encourages readers to consider their own experiences and the role and impact of multilingualism on the world around them. Accessibly written in an engaging style which assumes no prior knowledge, this book is an essential introduction for anybody interested in multilingualism and language."--